LCLS-II-HE Cryomodule Production Status at Fermilab. Issue 1 (1st May 2022) - Kaluzny, J; Arkan, T; Bice, D; Blowers, J; Checchin, M; Grimm, C; Hartsell, B; Martinello, M; Nicol, T; Posen, S; Premo, K
Abstract: The Linac Coherent Light Source (LCLS) is an X-ray science facility at SLAC National Accelerator Laboratory. The LCLS-II project (an upgrade to LCLS) is in its final stages, and the LCLS-II-HE (High Energy) project is another upgrade to the facility enabling higher energy operation. An electron beam is accelerated using superconducting radio frequency (SRF) cavities built into cryomodules. It is planned to build twenty-five modules total for the LCLS-II-HE project. Fourteen of these modules are planned to be assembled and tested at Fermilab. Procurements for production modules have been awarded, and parts are arriving. The design of the LCLS-II-HE modules is similar to the module design used in LCLS-II. The major cryomodule design change from LCLS-II is the nominal gradient required per cavity, increasing from 16 to 21 MV/m. The additional gradient yields additional heat loads. The first LCLS-II-HE cryomodule, referred to as the verification cryomodule (vCM), was assembled using parts from an LCLS-II module with new SRF cavities. The assembly is complete, and this module is currently being tested at Fermilab. The vCM cavities perform well, exceeding the required gradient and quality factor specifications. The first article module assembly is planned to start later in 2021. The status of the production as well as some of the design and assembly changes will be presented.